Predstavitev okvirov, ki jih Zavod za gozdove Slovenije uporablja pri izbiri drevja za posek v sestojih, namenjenih strojni sečnji - Beguš, Jurij (Gozdarski vestnik, 2009)
The article presents the development of mechanized felling in Slovenia and theSlovenian Forest Service's response to these trends. In addition, it presents the frameworks Slovenian Forest Service applies for selecting trees to be felled and preparing the work in the stands intended for mechanized felling.
Keywords: strojna sečnja; forestry; gozdarstvo; gozdni sestoji